PREDIKSI FINANCIAL DISTRESS BANK MENGGUNAKAN METODE BANKOMETER - Ani Nur Fadilah; Muhammad Rois; Rikawati (Lembaga Penerbit Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2024)
This study aims to predict bank financial distress in the Banking Sub-Sector Listed on the Indonesia Stock Exchange for the 2018-2022 period. The sampling technique was carried out by purposive sampling technique. Based on the sampling criteria, 2 banks listed on the Indonesia Stock Exchange were obtained which could be used as research samples. The method used is quantitative descriptive analysis. The financial ratios used in the Bankometer Method are Equity to Total Assets (EA), Loans to Total Assets (LA), Capital Adequacy Ratio (CAR), Capital to Total Assets (CA), Cost to Income Ratio (CI) and Non-Performing to Loan Ratio (NPL). The results of this study indicate that the average banking condition is very healthy (super sound), because the average S-Score value for the banking subsector is more than 70% during 2018-2022.